ANALISIS PENERAPAN KOMUNIKASI VIRTUAL PADA PEMBELAJARANEKONOMI DI MASA PANDEMI COVID-19 - Amir, Amir; Genjik, Bambang; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine planning in the application of virtual communication, the economic learning process in virtual communication, the inhibiting and supporting factors for the implementation of virtual communication in economics class X SMA Negeri 10 Pontianak. This research method uses a qualitative research type of case study research. The data sources for this research were an economics teacher and four. Data collection techniques are by observation, interviews and documentation. The results of this study indicate that the virtual communication media at SMA Negeri 10 Pontianak is using the smanpul e-learningapplication with teacher learning planning making online lesson plans, learning modules, student worksheets which are uploaded in the smanpul e-learning application. In the learning process the teacher starts from the opening activity by praying, being absent and conveying the learning objectives. The teacher's core activities direct to opening the material, studying the material and analyzing the material. closing activities the teacher concludes the material, evaluates the material. Inhibiting factors are lack of mastery of information technology, lack of internet network and no notifications in the smanpul e-learning application. The supporting factors are support from school principals, teachers, students and the school's need for educator- certified teachers.